Characteristics of Adult Cigarette Smokers Who "Relight" and the Effects of Exposure to Tobacco Smoke Constituents. Issue 9 (4th July 2018) - Allen, Sophia I; Wasserman, Emily; Veldheer, Susan; Yingst, Jessica; Hrabovsky, Shari; Liao, Jason; Krebs, Nicolle M; Horn, Kimberly; Reinhart, Lisa; Modesto, Jennifer; Putt, Kayla; Evins, A Eden; et al.
Abstract: Introduction: About half of smokers relight their cigarette, a habit that is a risk factor for chronic bronchitis and possibly lung cancer. Little is known about the characteristics of smokers who relight and their dependence on nicotine. It is unknown whether relighting affects exposure to tobacco smoke constituents. This study examined the characteristics of relighters of usual brand cigarettes and whether relighting affects exposure to selected tobacco smoke constituents. Methods: We explored relighting status and frequency, using baseline data from 248 adult smokers participating in studies of reduced nicotine cigarettes in relation to demographic and cigarette characteristics, smoking behaviors, nicotine dependence, biomarkers of exposure (exhaled carbon monoxide, blood cotinine), and biomarkers of oxidative stress (ratio of oxidized/reduced glutathione). Results: 69.4% ( n = 172) of subjects reported relighting, and they relit an average of five cigarettes out of 20. Both relighters and non-relighters smoked a mean of 20 cigarettes per day ( p = .6). Relighting was significantly associated with higher nicotine dependence, use of longer rod cigarettes, older age, lower income, and unemployment. There were no significant associations between relighting and blood cotinine, exhaled carbon monoxide or measures of oxidized/reduced blood glutathione. Conclusions: The majority of subjects were relighters, who had higher levels of nicotine dependence than non-relighters. Relighters had similar levels of plasma cotinine and exhaled carbon monoxide to non-relighters. Implications: No study has compared the cigarette characteristics and biomarkers of exposure of adult cigarette smokers who relight with those who do not. Relighting behavior was common in our sample and was associated with low income, not currently working, higher nicotine dependence, cigarette rod length, daily cigarette use years, and a lifetime history of depressed mood.